Community empowerment through home care training to improve the quality of life of patients - Trimaya Cahya Mulat; Wahyudi Hardi; Nur Andani (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2024)
Community empowerment is one of the effective strategies to improve patient's quality of life by increasing the capacity of families and communities to provide home care. This service aims to evaluate the impact of home care training on the quality of life of patients with chronic health conditions treated at home. The methods used in the training include theory, practical simulations, and group discussions. The evaluation results showed that the trainees experienced an increase in knowledge and skills in providing home care, which positively impacted patients' quality of life. The program empowers families to treat patients more effectively and reduces the burden on the formal health system by optimizing care at home. This activity concludes that home care training is an effective strategy for community empowerment to improve patients' quality of life and support the sustainability of health care in the community